Russian military intervention in Syria in years 2015-2020 - Barkhatov, Dmitriy; Eichler, Jan, 1952-; Dubský, Zbyněk, 1974-; Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů (2020)
The thesis tries to answer 2 questions: what actually motivated Russia to carry out military intervention to Syria and whether the military presence was successful or not. Based on the neorealist paradigm we would look at various aspects of the intervention that can be crucial for the evaluation process. Going from geostrategic, ideological, military and political aspects we would be able to judge what aspect played the most important role in decision-making regarding the intervention. As a result, we would come with an objective speculation of the main purpose of the military campaign and whether the intervention was successful. Some of the conflict features are also going to be omitted – in this publication we will not talk about the whole relationship structure in the region, neither we would discuss the activities of the International Coalition. The activities that are related purely to Russia and Syria in a global context are going to be presented through Russian perspective.
Vedoucí práce: Jan Eichler
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta mezinárodních vztahů, 2020
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2020
Způsob přístupu: Internet
Keywords: mezinárodní politika a diplomacie [obor dipl. práce]; diplomové práce; master's theses